Blood serum IgE and muscle element levels in Cyprinus carpio infested by Argulus foliaceus in Lake Çavuşçu (Konya/Turkey): Assessment of their impact on human health - Gümüş Numan Emre (Oceanological and Hydrobiological Studies)
Fish with the metazoan parasite Argulus foliaceus (Crustacea: Branchiura) infestation observed in carp (Cyprinus carpio) were caught between September and October 2018 in Lake Çavuşçu. The objective of this study was to determine the concentrations of selected heavy metals (Cd, Co, Cr, Cu, Fe, Mn, Mo, Ni, Pb, Se, Zn) in the muscle tissue of individuals of this fish species. The levels of heavy metals were studied and assessed for their effects on human health. The results obtained in the study were compared with the limit values set by national and international quality criteria. In addition, blood serum IgE levels were examined in fish. IgE is considered part of the parasite-specific immune defense system called allergic antibody. The results were compared with serum IgE levels in non-parasitized carp. It was found that serum IgE levels of infested fish were higher than serum IgE levels of non-parasitized carp. The recommendation for consumers is that although the target hazard quotient (THQ) and total target hazard quotient (TTHQ) were well below 1, they should be mindful of the risk in their daily fish intake.